Predicting future default on the Covid-19 bounce back loan scheme: The £46.5 billion question. (August 2022) - Cowling, Marc; Wilson, Nick; Nightingale, Paul; Kacer, Marek
The UK has had a commitment to loan guarantee schemes since 1981 when it introduced the Small Firms Loan Guarantee (SFLG) scheme to address access to debt finance issues for smaller firms. Over the last 40 years, its support has been unwavering, and in the Covid-19 crisis, it once again turned to loan guarantees as a means of supporting smaller firms through the crisis-induced slump in trading activities. Of its three core Covid-19 guarantee schemes, the Bounce Back Loan (BBL) scheme was the most numerous with 1, 531, 095 loans issued amounting to a total of £46.5bn in lending. The BBL scheme provided a 100% capital guarantee on loans between £2, 000 and £50, 000, and firms were allowed to borrow up to 25% of their trading income, with a fixed interest rate of 2.5% of which the first years interest was paid by the government to the lending bank. Our findings suggest that the government losses may range between £7bn and £12bn depending on the underlying assumptions; however, we estimate Covid-19 guarantee schemes may have protected 118, 639 businesses and 1, 117, 849 jobs. Looking to the future, we suggest that a new loan guarantee is justified that more resembles the former SFLG than the restrictive Enterprise Finance Guarantee (EFG) as more than one million small businesses will be heavily indebted and unable to borrow to invest in future growth opportunities. This would support the 'levelling-up' agenda and help prevent a post-Covid-19 low investment–low growth scenario.